2023
DOI: 10.3389/fphar.2023.1067085
|View full text |Cite
|
Sign up to set email alerts
|

Eldecalcitol prevented OVX-induced osteoporosis through inhibiting BMSCs senescence by regulating the SIRT1-Nrf2 signal

Abstract: Background: Aging and oxidative stress are considered to be the proximal culprits of postmenopausal osteoporosis. Eldecalcitol (ED-71), a new active vitamin D derivative, has shown a good therapeutic effect on different types of osteoporosis, but the mechanism is unclear. This study focused on exploring whether ED-71 could prevent bone loss in postmenopausal osteoporosis by regulating the cell senescence of bone mesenchymal stem cells (BMSCs), and explaining its specific mechanism of action.Materials and metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“… 31 In order to explore the effect of ED-71 on osteoclasts, we established the postmenopausal osteoporosis model in rats based on our previous report. 26 Our results showed that the tibial bone mass and the new bone formation was reduced, indicating the successful establishment of the model. The postmenopausal osteoporosis is found to be in a state of oxidative stress.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“… 31 In order to explore the effect of ED-71 on osteoclasts, we established the postmenopausal osteoporosis model in rats based on our previous report. 26 Our results showed that the tibial bone mass and the new bone formation was reduced, indicating the successful establishment of the model. The postmenopausal osteoporosis is found to be in a state of oxidative stress.…”
Section: Discussionmentioning
confidence: 50%
“… 32 We used H 2 O 2 stimulated MC3T3-E1 cells as in vitro model, simulating those growing in osteoporosis environment. 26 The results showed that H 2 O 2 increased osteoclast generation, as well as the protein and mRNA expression of CtsK and MMP9, both are related to the ability of osteoclast to undergo bone resorption.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…showed that melatonin promotes the osteogenic potential of BMSCs by regulating SIRT1-mediated antioxidant properties [29]. Eldecalcitol inhibits BMSC senescence by modulating the SIRT1-Nrf2 pathway [60]. Based on these findings, we further investigate whether carvacrol regulates SIRT1 to influence the osteogenic differentiation of BMSCs.…”
Section: Discussionmentioning
confidence: 83%
“…Upregulation of NRF2 has been suggested as a mechanism for reduced cellular senescence in models of diseases such as osteoporosis [ 180 ], age-related macular degeneration [ 181 ], age-related cognitive decline [ 182 ] and renal fibrosis [ 183 ]. Recently, Liu et al described how NRF2 is activated during DOX-induced senescence in two human cancer cell lines and in vivo by an accumulation of the oncogene iASPP (Inhibitor of Apoptosis Stimulating Protein of P53), which binds and inhibits KEAP1 [ 184 , 185 ].…”
Section: Drug-induced Cardiotoxicity and The Role Of Nrf2mentioning
confidence: 99%